Employees’ Welfare and Productivity Relations - Kolawole, Kayode David (Indonesian Academy of Social and Religious Research (IASRR), 2024)
Employee welfare initiatives such as working arrangement flexibility, health programs, and recognition programs can motivate them and result in increased productivity. The paper aims to: examine how employees’ welfare affects their productivity; assess the role of employees’ health and safety in workers’ productivity, investigate retirement benefit in workers’ productivity, assess the role of workplace flexibility in workers’ productivity and assess the impact of vacation benefit on workers’ productivity. The study used survey methods to gather responses from the respondents. The data gather from Section A was using simple percentages while data for section B was analyzed using both simple percentages and chi-square analysis. The findings reveal that there is a significant relationship between employees’ health and safety and workers’ productivity. There is a significant relationship between retirement benefit and workers’ productivity. There is a significant relationship between vacation benefit and workers’ productivity. There is no significant relationship between workplace flexibility and productivity. . Overall, the evidence shows that welfare plays a crucial role in influencing the productivity of workers, however this depends on the nature of the welfare program. The paper recommends the need for management to provide a comprehensive benefits package that includes health insurance, retirement plans, paid time off, and other perks like flexible work hours, remote work options, and employee discounts.